2-Phenylindole derivatives as anticancer agents: synthesis and screening against murine melanoma, human lung and breast cancer cell lines. Issue 17 (2nd September 2019) - Gaikwad, Ruchi; Bobde, Yamini; Ganesh, Routholla; Patel, Tarun; Rathore, Anju; Ghosh, Balaram; Das, Kalpataru; Gayen, Shovanlal
Abstract: Indole derivatives have attractive anticancer properties and may be a future hope for better anticancer drug(s) of low toxicity and high potency. In this paper, syntheses of 2-phenylindole derivatives have been described via Fischer indole synthesis through a one-pot solvent-free method. The synthesized compounds were screened for anticancer potential in vitro against murine melanoma (B16F10), human lung cancer (A549), and human breast cancer (MDA-MB-231) cell lines. The results highlighted that 2-phenylindole derivatives are also promising anticancer agents in case of melanoma and lung cancer along with the breast cancer. Molecular docking analyses with possible targets for melanoma (NEDD4-1) and lung cancer (EGFR) were also performed to understand specific interactions of 2-phenylindole derivatives with the amino acid residues of the receptors. GRAPHICAL ABSTRACT: UF0001